2022
DOI: 10.3390/ijerph192114576
|View full text |Cite
|
Sign up to set email alerts
|

Migration for Better Jobs or Better Living: Shifts in China

Abstract: Traditionally, studies of mobility follow two main strands: migration driven by better jobs and by better living. However, the interactions and shifts between them are rarely addressed. In the largest-scale domestic migration, millions of Chinese movers have experienced changes in migration motivations in the past ten years. Starting with migration patterns, we attempt to explore the interaction and changes in migration motivations in a dynamic way and relate them to the evolution of socio-economic contexts. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…A study on the impact of the household registration system reform indicates that between 2000 and 2014, cities in the eastern regions gained roughly 135% more migrants than those in the middle of the country and roughly 245% more than cities in the western regions. The study also revealed that smaller cities, with populations between one and two million people, experienced the greatest growth during that period [43]. The Bureau of Statistics data from the seventh national census (2020) shows that the provinces/regions with the largest proportion of floating populations were the Yangtze River Delta (15.9%), Guangdong (13.9%), Zhejiang (6.8%), Jiangsu (6.3%), and Henan (5.6%) (see Figure 5).…”
Section: Fast-growing Cities Mean High Migrationmentioning
confidence: 84%
See 1 more Smart Citation
“…A study on the impact of the household registration system reform indicates that between 2000 and 2014, cities in the eastern regions gained roughly 135% more migrants than those in the middle of the country and roughly 245% more than cities in the western regions. The study also revealed that smaller cities, with populations between one and two million people, experienced the greatest growth during that period [43]. The Bureau of Statistics data from the seventh national census (2020) shows that the provinces/regions with the largest proportion of floating populations were the Yangtze River Delta (15.9%), Guangdong (13.9%), Zhejiang (6.8%), Jiangsu (6.3%), and Henan (5.6%) (see Figure 5).…”
Section: Fast-growing Cities Mean High Migrationmentioning
confidence: 84%
“…Historically, scholars have considered employment as one of the most prominent factors driving internal migration [1,6,42,43]. Some people move if there is a better job or better pay elsewhere [37,38].…”
Section: Moving For Employmentmentioning
confidence: 99%